2021
DOI: 10.1002/nme.6703
|View full text |Cite
|
Sign up to set email alerts
|

A unified algorithm for the selection of collocation stencils for convex, concave, and singular problems

Abstract: We introduce in this article a unified algorithm which allows the selection of collocation stencils, based on the visibility criterion, for convex, concave, and singular problems solved using a collocation method. The algorithm can be applied to any 2D or 3D problem. We show the importance of using a threshold angle, in conjunction with the visibility criterion, to assess of the inclusion of a node in the support of a collocation center. We also show how the algorithm can be used to assess the presence of a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…We used this approach. The algorithms presented in reference [33] or in reference [2] are alternative algorithms that use boundary nodes and elements to decide upon the inclusion of nodes in the domain. Other algorithms such as the "crossing number" or the "winding number" methods, described in references [34,35,36], can be used in 2D.…”
Section: Domain Discretizationmentioning
confidence: 99%
See 3 more Smart Citations
“…We used this approach. The algorithms presented in reference [33] or in reference [2] are alternative algorithms that use boundary nodes and elements to decide upon the inclusion of nodes in the domain. Other algorithms such as the "crossing number" or the "winding number" methods, described in references [34,35,36], can be used in 2D.…”
Section: Domain Discretizationmentioning
confidence: 99%
“…• the connections to other boundary nodes if boundary elements are used to enforce the generalized visibility criterion [2] or to speed-up the refinement of the surface.…”
Section: From Discretization To Smart Cloudmentioning
confidence: 99%
See 2 more Smart Citations
“…In context of RBF-FD the topic has been thoroughly investigated in adaptive solution of Poisson's equation [26], including the problems with point singularities [23]. In [28], the authors present a method for stencil selection, based on the visibility criterion, for convex, concave, and singular problems in 2D and 3D. In [26,23] authors demonstrated effective stencils of 6 or 5 nearby points that are sufficiently uniformly distributed around central node to support RBF-FD, and successfully solved several test problems.…”
Section: Introductionmentioning
confidence: 99%